Understanding of life and acceptance of death. The stoic management of grief on Seneca’s «Consolations» - Linares Huertas, Omar (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Philosophy has therapeutic potential since its Greek origins. Among all Hellenistic Schools, it could be said that the most concerned about human suffering was the Stoic one. This paper analyzes the Stoic management of the grief found on Seneca’s Consolations, showing the therapeutic operativity of his proposal as explanatory-experiential methodology with eudemonic or sapiential goals.